Evaluación del uso de bacterias fijadoras de nitrógeno en el cultivo de banano - Haro Correa, Gabriel Ignacio (2012)
The investigation on the Evaluation of the use of Nitrogen Fixer bacteria in the cultivation of Banana crop, 2012 was carried out in the property La Clotilde located in the site Caña Quemada, it had the following objectives: 1. To determine the benefit of applying nitrogen fixer bacteria in the banana crop. 2. To calculate the reduction percentage of nitrogenated fertilizers in function from the dose of applied bacteria to the soil and, 3. To establish the relationship cluster-boxes. The applied treatments to the experimental units with 10 useful plants, distributed in Blocks at Random: T1 Twin N + Urea 100%; T2 Twin N + 25% of Carbamide; T3 Twin N + 50% of Carbamide; T4 Twin N + 75% of N; T5 Twin N + 100% of Carbamide; T6 Carbamide 100% and T7 absolute control. The bacteria Twin N was applied by means of aspersion to the soil. The valued variables were: Capacity of cationic exchange to the beginning and the end, Percentage of organic matter to the beginning and the end; Height of the son to 60 and 90 days; Number of leaves to 30, 60 and 90 days; width of Pseudo stem to 30, 60 and 90 days; Days to the birth; Initial and final radicular volume; Number of hands of the bunch; Weigh of the cluster and Ratio. In the variance analyses it was not significant results for the plant height, width of the stem and number of leaves in the periods of sampling at 30, 60, 90 and 120 days; while, in the treatments it influenced on the weight of the bunch, number of hands per bunch, profitable fruit and ratio. The treatments combining the application of Twin N + Carbamide, gave highly significant results in the number of hands per bunch, weight of the cluster, exportable fruit and in the ratio. The best option from the point of view of production of exportable fruit and productivity of the plantation was obtained with the treatment T5 Twin N 100% + Carbamide 100%, reaching an increment of 64% on the absolute witness and 21% on the conventional treatment with Carbamide 46%, (treatment T6). The biggest ratio with 1,31 was reached with the treatment T5 (Twin N 100% + Carbamide 46%, the entirety of the fertilization doses/cycle.